2015
DOI: 10.1007/s10231-015-0503-1
|View full text |Cite
|
Sign up to set email alerts
|

Sup-norm-closable bilinear forms and Lagrangians

Abstract: Abstract. We consider symmetric non-negative definite bilinear forms on algebras of bounded real valued functions and investigate closability with respect to the supremum norm. In particular, any Dirichlet form gives rise to a sup-norm closable bilinear form. Under mild conditions a sup-norm closable bilinear form admits finitely additive energy measures. If, in addition, there exists a (countably additive) energy dominant measure, then a sup-norm closable bilinear form can be turned into a Dirichlet form admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 77 publications
0
24
0
Order By: Relevance
“…By the arguments of [, Lemma 1.4.2 and Problem 1.4.1] the algebra scriptA provides a special standard core for (E,F). Combining [, Corollary 7.1.2] and [, Corollary 8.3] we obtain .…”
Section: Local Dirichlet Forms On Carpet‐like Spacesmentioning
confidence: 91%
See 2 more Smart Citations
“…By the arguments of [, Lemma 1.4.2 and Problem 1.4.1] the algebra scriptA provides a special standard core for (E,F). Combining [, Corollary 7.1.2] and [, Corollary 8.3] we obtain .…”
Section: Local Dirichlet Forms On Carpet‐like Spacesmentioning
confidence: 91%
“…Our paper is a part of a broader program that aims to connect research on derivatives on fractals ( [8,9,[13][14][15][25][26][27][28]31,33,35,[37][38][39][40][41]46,51,54] and references therein) and on more general regular Dirichlet spaces [29,30,34] with classical and geometric analysis on metric measure spaces ( [6,10,12,[21][22][23][24][42][43][44][45]50] and references therein). In our previous article [36] we showed that on certain topologically one-dimensional spaces with a strongly local regular Dirichlet form one can prove a natural version of the Hodge theorem for 1-forms defined in 2 -sense: the set of harmonic 1-forms is dense in the orthogonal complement of the exact 1-forms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 6 displays this most extreme case. Using (24) and the triangle inequality we can then see that the maximal difference of the values on f on these points is bounded by 4 −n 7 L E ∂Ω (f ). By averaging then also the difference of g n (x) and g n (x ) is bounded by that number.…”
Section: 1mentioning
confidence: 99%
“…Remark 6.2. In some sense Corollary 6.1 and formula (24) imply not only that g is Euclidean-Lipschitz, but also that g has "zero (Euclidean) tangential derivative" along ∂Ω, because an E ∂Ω -intrinsic Lipschitz function has to grow "infinitely slow" in the "tangential direction" to the Koch curve.…”
Section: 1mentioning
confidence: 99%